2013
DOI: 10.1158/0008-5472.can-12-2233
|View full text |Cite|
|
Sign up to set email alerts
|

LOX-Mediated Collagen Crosslinking Is Responsible for Fibrosis-Enhanced Metastasis

Abstract: Tumor metastasis is a highly complex, dynamic, and inefficient process involving multiple steps, yet it accounts for more than 90% of cancer-related deaths. Although it has long been known that fibrotic signals enhance tumor progression and metastasis, the underlying molecular mechanisms are still unclear. Identifying events involved in creating environments that promote metastatic colonization and growth are critical for the development of effective cancer therapies. Here, we show a critical role for lysyl ox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
426
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 457 publications
(446 citation statements)
references
References 48 publications
15
426
3
2
Order By: Relevance
“…To that end, it has been proposed that the treatment of underlying fibrosis in such cases would lead to an improvement in cancer associated prognosis [13]. In our work last year, we showed that tissue fibrosis may pose a serious clinical problem in patients harboring unrelated primary tumors [6]. The presence of pathological organ fibrosis in both the lung and the liver increases the ability of circulating breast cancer cells to colonize and grow in these organs, suggesting that breast cancer patients with unrelated organ fibrosis may present a poorer metastasis-free survival.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…To that end, it has been proposed that the treatment of underlying fibrosis in such cases would lead to an improvement in cancer associated prognosis [13]. In our work last year, we showed that tissue fibrosis may pose a serious clinical problem in patients harboring unrelated primary tumors [6]. The presence of pathological organ fibrosis in both the lung and the liver increases the ability of circulating breast cancer cells to colonize and grow in these organs, suggesting that breast cancer patients with unrelated organ fibrosis may present a poorer metastasis-free survival.…”
mentioning
confidence: 79%
“…Early on in tumorigenesis, this homeostasis is upset and the ECM begins to change in both its biochemical as well as its biomechanical properties. In the case of breast cancer, it has been shown that these desmoplastic changes, driven primarily by collagen I accumulation, are a key component of the tumor microenvironment [1] and act to drive malignant transformation [2], but also drive tumor progression [3,4] and ultimately metastasis [5,6]. Yet this disruption to homeostatic ECM mechanisms is not confined to the primary tumor site.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work using fibrosarcoma HT-1080 cells found that the matrix at the leading edge of a single cell undergoes reversible deformation during mesenchymal migration in 3D collagen matrix (Bloom et al 2008). Glioma cells were also found to secrete lysyl oxidase (LOX), a collagen crosslinker, promoting invasive behaviors (Laczko et al 2007;Cox et al 2013). Our results indicated that these modifications of the local network lead to the formation of a stiffer microenvironment at the leading edge of the mesenchymal migrating cell.…”
Section: Nhs-microspheres Can Measure the Mechanics Of Varying Microementioning
confidence: 99%